1990
DOI: 10.1246/cl.1990.2269
|View full text |Cite
|
Sign up to set email alerts
|

Benzenetellurinic Mixed Anhydrides as Mild Oxidizing Agents

Abstract: Three benzenetellurinic mixed anhydrides, i.e., benzenetellurinyl acetate, trifluoroacetate, and trifluoromethanesulfonate, have been found to be mild oxidizing agents for various substrates such as thiol, phosphine, acyloin, α-hydroxy ester, catechol, hydroquinone, thiourea, and thioamide. The reactions towards the last two substrates are highly chemoselective, depending on both the reagent and substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The reported methods for the preparation of 3,5-diaryl-1,2,4-thiadiazoles from the corresponding thioamides include using different oxidants such as hypervalent iodine, 3 dimethyl sulfoxide (DMSO)/2-chloro-1,3-dimethylimidazolinium chloride (DMC), 8 DMSO/haloiminium salt, 9 DMSO/HCl, 7 methanesulfonic acid derivative with benzenetellurinic acid, 10 and telluroxide or selenoxide. 11 Other more complicated methods are also reported: from the corresponding oxathiazolone, 12 benzenecarboximidamide and diethyl azodicarboxylate, 13 or from 1,2,4-oxathiazoles and Lewis acid.…”
Section: Resultsmentioning
confidence: 99%
“…The reported methods for the preparation of 3,5-diaryl-1,2,4-thiadiazoles from the corresponding thioamides include using different oxidants such as hypervalent iodine, 3 dimethyl sulfoxide (DMSO)/2-chloro-1,3-dimethylimidazolinium chloride (DMC), 8 DMSO/haloiminium salt, 9 DMSO/HCl, 7 methanesulfonic acid derivative with benzenetellurinic acid, 10 and telluroxide or selenoxide. 11 Other more complicated methods are also reported: from the corresponding oxathiazolone, 12 benzenecarboximidamide and diethyl azodicarboxylate, 13 or from 1,2,4-oxathiazoles and Lewis acid.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that the Ph 3 BiCl 2 ‐mediated process is selective as the reaction stopped at the dehydrosulfurization stage with no further reaction towards dimeric thiadiazoles. The latter could have been generated in situ by condensation of the produced nitriles with the starting thioamides, as previously observed by others …”
Section: Resultsmentioning
confidence: 71%
“…From Table 1, CuBr was chosen as the best catalyst. Then a series of solvents were examined (Table 1, entries [12][13][14][15][16]. It was showed that the reaction gave the product with 89% yield when it was performed in ClCH 2 CH 2 Cl (Table 1, entry 7).…”
Section: Resultsmentioning
confidence: 99%